2018
DOI: 10.1371/journal.pone.0190700
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and reproductive performance of a specialist herbivore depend on seasonality of, and light conditions experienced by, the host plant

Abstract: Host plant phenology (as influenced by seasonality) and light-mediated changes in the phenotypic and phytochemical properties of leaves have been hypothesised to equivocally influence insect herbivore performance. Here, we examined the effects of seasonality, through host plant phenology (late growth-season = autumn vs flowering-season = winter) and light environment (shade vs full-sun habitat) on the leaf characteristics of the invasive alien plant, Chromolaena odorata. In addition, the performance of a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Moreover, seasonal changes in water supply can alter physiological characteristics such as turgor pressure (Mitchell et al 2008;Simpson et al 2012) and water content (Claussen 2005;Fernàndez-Martínez et al 2013) and, thereby, influence plant palatability (Huberty and Denno 2004). In addition, traits related to structural defenses including tissue toughness and cuticle thickness have been reported to vary across seasons (Gotsch et al 2010) and may contribute to circannual patterns of herbivore resistance (Peeters 2002;Uyi et al 2018). Hence, plant resistance to herbivores and herbivore performance may be influenced by a wide variety of plant traits apart from plant defense metabolites (Hu et al 2018;Huang et al 2019).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Moreover, seasonal changes in water supply can alter physiological characteristics such as turgor pressure (Mitchell et al 2008;Simpson et al 2012) and water content (Claussen 2005;Fernàndez-Martínez et al 2013) and, thereby, influence plant palatability (Huberty and Denno 2004). In addition, traits related to structural defenses including tissue toughness and cuticle thickness have been reported to vary across seasons (Gotsch et al 2010) and may contribute to circannual patterns of herbivore resistance (Peeters 2002;Uyi et al 2018). Hence, plant resistance to herbivores and herbivore performance may be influenced by a wide variety of plant traits apart from plant defense metabolites (Hu et al 2018;Huang et al 2019).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, the equal reproductive performance of moths fed on full-sun and shaded foliage is inconsistent with the CNB hypothesis and does not appear to extinguish the debates surrounding the hypothesis in terms of herbivore performance. Although, the CNB hypothesis predicts that leaves from plants in shaded environments are more suitable sources of food for insect herbivores and that herbivorous insects would perform better on such leaves, empirical evidence often suggests variable patterns [3][4][5]8,9,11,42 .…”
Section: Correlations Between Leaf Consumption and Herbivore Performamentioning
confidence: 99%
“…Conspecific plant species vary their leaf chemistry and phenotypic characteristics when grown in different habitats 1 4 . Herbivorous insects, in turn, are affected by these differences, with complex variations in their performance in response to leaf properties 5 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Individual plants of the same species often exhibit a range of physical and chemical differences based on abiotic factors such as light intensity, rainfall, soil composition, and temperature (Bisigato et al 2015;Boege & Dirzo 2004;Sarfraz et al 2013;Uyi et al 2017). Intraspecific variation in plant characteristics is commonly found among different light environments (Barber & Marquis 2011;Ingersoll et al 2010;Osier & Jennings 2007;Wyka et al 2012), since light intensity can directly affect the photosynthetic rate of plants, influencing morphological, physiological and biochemical processes (Mathur et al 2018;Uyi et al 2018;Zhang & Wen 2009).…”
Section: Introduction _______________________________________________mentioning
confidence: 99%
“…Nutrient content is also thought to play a major role in determining insect performance. Nitrogen is thought to often be the limiting nutrient for insect herbivores (Mattson 1980;Uyi et al 2018), since many studies have shown that insects perform better on foliage with higher nitrogen content. For instance, Osier and Jennings (2007), found that foliar nitrogen content was the strongest determinant for insect performance for promethea moth (Callosamia promethea); larval mass, survivorship, and developmental rate were positively correlated with foliar nitrogen (Osier & Jennings 2007).…”
Section: Introduction _______________________________________________mentioning
confidence: 99%